Parallel Algorithm for the Quasi-TEM Analysis of Microstrip Multiconductor Line - Pomarnacki, R.; Krukonis, A.; Urbanavičius, V. (Elektronika ir Elektrotechnika, 2010)
Presented parallel algorithm for the quasi-static microstrip multiconductor lines (MMCL) analysis, with optional conductor number, width and spaces between conductors. To apply MMCL as a physical model for various microstrip devises design, for example, meander microstrip delay lines, it is sufficient to study only quasi-static parameters of the MMCL inducing c- or -normal waves. As analysis method in the proposed parallel algorithm any numerical quasi-static approach may be used. Authors have implemented an algorithm in five computer cluster using the finite difference method. For calculation procedure speed up the potential distribution of the MMCL was calculated using band matrix technique and sparse matrix approach. The proposed parallel algorithm was tested in four- and five-conductors MMCL. Authors obtained results that differ from those of other investigators and the results obtained by other means no more than 3 %. It was found that the proposed parallel algorithm allows speed up of calculations up to 3.6 times.